Avifauna of Pashukhali and Gajdhar village in Netrokona district, Bangladesh (Bangladesh Journal of Zoology, 2015)
Avifauna of village Pashukhali and Gajdhar in the district of Netrokona, Bangladesh was carried out during July 2003-June 2004. A total of 101 species of birds belonging to 12 orders, 35 families and 82 genera were recorded. Out of 101 species, 61 (60.4%) were non-passerine and 40 (39.6%) were passerine. Among them, 80 (79.2%) were resident and 21 (20.8%) were migratory birds. Of the non-passerine birds, 15 (24.6%) were migratory and 46 were (75.4%) resident. While in passerine birds, 6 (15%) were migratory and 34 (85%) were resident. Of the total species, 18 (17.8%) were locally found to be very common, 41 (40.6%) were common, 29 (28.7%) fairly common and 13 (12.9%) rare or few. Out of 101 species, highest numbers (58.4%) of species were widely distributed. Maximum numbers of birds (78.2%) were terrestrial.Bangladesh J. Zool. 42(2): 141-152, 2014